Towards Safety Driving: How Neuroticism Affects Malaysian Drivers’ Behaviour - Rosli, Nur Shazwani; Mohd Yunus, Jasmani; Abdul Hanan, Suhaila (Asian Online Journals, 2018)
The aim of this study is to examine the relationship between neuroticism of Big 5 personality and adverse driving behaviour among motorists in Malaysia. Intercepted drivers were surveyed using self-reported questionnaires, and they were asked their opinions about their driving behaviour as well as their personality traits. A total of 384 completed questionnaires were collected with a response rate of 18.1 per cent. However, only 311 were found useable for the final analysis. Partial Least Squares (PLS) path modelling was used in the data analysis. The finding revealed a significant and positive relationship between neuroticism and adverse driving behaviour. Keyword Adverse Driving B